Larval morphology of Allodessus Guignot (Coleoptera: Dytiscidae) - Michat, Mariano Cruz (2011)
The three larval instars of the type species of the bidessine genus Allodessus Guignot (A. bistrigatus (Clark)) are described and illustrated for the first time including detailed morphometric and chaetotaxic analyses of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphi. Larvae of this genus are characterised by the absence of the primary pore ABc, which is a synapomorphy of the tribe Bidessini, and the presence of secondary setae on the urogomphi, which suggest a close phylogenetic relationship with Amarodytes Régimbart. Allodessus larvae are further characterised by a short last abdominal segment, long urogomphi, absence of colour pattern on the body, presence of a ventroapical spinula on the third antennomere, presence of pore PAk, presence of posterior secondary setae on coxa, presence of a large number of secondary setae on coxa, presence of posteroventral secondary setae on tarsus, and presence of a total of 6-7 (instar II) and 7-11 (instar III) secondary setae on metatarsus. This combination of characters separates larvae of Allodessus from those of the other known Bidessini genera.